Measuring inconsistencies can lead you forward: Imageability and the x-ception theory - Dellantonio, Sara; Mulatti, Claudio; Pastore, Luigi; Job, Remo (Frontiers in Psychology, 2014)
According to the traditional view, both imageability and concreteness ratings reflect the way word meanings rely on information mediated by the senses. As a consequence, the two measures should and do correlate. The link between these two indexes was already hypothesized and demonstrated by Paivio, Yuille & Madigan (1968) in a seminal article, where they introduced the idea of imageability ratings for the first time. However, in this first study, they also noted a contrasting pattern in the ratings for imageability and concreteness with some words that refer to affective attitudes or emotional states receiving high imageability but low concreteness ratings. Recent studies confirm this inconsistency (e.g., Altarriba & Bauer, 2004) leading to the claim that emotion words form a particular class of terms different from both concrete and abstract words. Here we use the MRC psycholinguistic database to show that the there are other classes of terms for which imageability and concreteness are uncorrelated. We show that the common feature of these word classes is that they directly or indirectly refer to proprioceptive, interoceptive, or affective states, i.e. to internal, body-related, sensory experiences. Thus, imageability and concreteness can no longer be considered interchangeable constructs; rather, imageability is a different, and perhaps more interesting, measure: it not only reflects the ease with which memories of external events come to mind, as previously hypothesized, but also reflects the ease with which memories of internal events come to mind.